Особливості кристалохімічного стану катіонів заліза в синтетичних магнітовпорядкованих наночастинках оксидів і гідроксидів заліза за даними мессбауерівської спектроскопії - Іваницький, В.П.; Брик, О.Б.; Дудченко, Н.О.; Польшин, Е.В.; Калініченко, О.А. (Мінералогічний журнал, 2011)
За допомогою методу мессбауерівської спектроскопії на ядрах ⁵⁷Fe вивчено фазовий склад шести зразків магнітовпорядкованих наночастинок, створених за різними технологіями. Визначено валентний стан структурних катіонів заліза, їх розподіл по фазах та нееквівалентних структурних позиціях, внутрішні магнітні поля на ядрах резонансних іонів, а також вплив розмірів наночастинок на формування спектроскопічних параметрів. Отримані результати можуть бути використані для розробки технологій синтезу магнітовпорядкованих наночастинок з властивостями, близькими до властивостей біогенних магнітних наномінералів. C помощью метода мессбауэровской спектроскопии на ядрах ⁵⁷Fe изучен фазовый состав шести образцов магнитоупорядоченных наночастиц, созданных по разным технологиям. Определены валентное состояние структурных катионов железа, распределение их по фазам и неэквивалентным позициям, внутренние магнитные поля на ядрах резонансных ионов, а также влияние размеров наночастиц на формирование спектроскопических параметров. Результаты могут быть использованы для разработки и усовершенствования технологий синтеза магнитоупорядоченных наночастиц со свойствами, близкими к свойствам биогенных магнитных наноминералов. The phase composition of six samples of magnetic-ordered nanoparticles, created by different technologies, were studied using method of ⁵⁷Fe Mössbauer spectroscopy. According to the data of transmission electron microscopy, the size of the particles of different samples ranged from 40 to 100 nm. Mössbauer spectra of the samples are pre sented by sextets of magnetic splitting, associated with the resonance absorption of ⁵⁷Fe in different phases. The nomenclature of the phases and their relationship are different for each sample. Among the pha ses represented in the samples there are non stoi chio metric magnetite, mag hemite, hematite and goethite in different combinations. The content of magnetite in the samples ranged from 28 to 100 %. The area ratio of the absorption lines (concentrations) of Fe³⁺ ions in tetrahedral (A) and octahedral (B ) positions of magnetite structure to the Fe³⁺ and Fe²⁺ ions in octahedral positions (SA /SB) ranged from 1.016 to 1.621 (scheme 1) and from 0.988 to 2.007 (scheme 2). Deviation of the ratio SA /SB from the value of 0.5, characteristic for the stoichiometric magne tite, indicates a significant oxidation of Fe²⁺ ions in oc tahedral positions. The content of goethite in four samples ranged from 42 to 81 %. The structure of goethite is cha racterized by a high degree of watering. The presence of water in the structure leads to appearance of four non-equivalent positions of the cations Fe³⁺, detected in the individual sextets. Hematite in the amount of 12—13 % was identified in two samples and maghemite (100 %) in one. The valence state of iron structural cations, their distribution by phases and non-equivalent positions, inte rior magnetic fields on the resonance ions’ nuclei and the influence of nanoparticles’ size on the formation of spectroscopic parameters were determined. The obtained results could be used for development and improvement of synthesis technologies of magnetic-ordered nanoparticles with special properties that are similar to the properties of their biogenic analogues.